2006
DOI: 10.1007/s10658-005-3479-7
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Resistance and Cost of Virulence

Abstract: A seasonal model, where a growing season is defined as the time between sowing and harvest and alternates with an inter-crop period, was derived to study the effects of the 'cost of virulence' and cropping ratio on durability of resistance. We assumed a single strain of virulent pathogen, a single strain of avirulent pathogen and two cultivars (one resistant and one susceptible) and studied two measures of durability of resistance ('take-over time' and 'usefulness time'). Take-over time is defined as the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 19 publications
(17 reference statements)
7
23
0
Order By: Relevance
“…napus pathosystem provide experimental evidence for a fungal pathogen that it may be possible to predict durability of R genes introduced into new cultivars by assessing the fitness cost of virulence. This supports theoretical evidence and experimental evidence with bacterial pathogens (Leach et al 2001;Pringle and Taylor 2002;Pietravalle et al 2006;Bent and Mackey 2007). The evidence that fitness cost of virulence at the AvrLm4 locus is generally greater than that at the AvrLm1 locus suggests that the corresponding resistance gene Rlm4 may be more durable than Rlm1 when it is deployed in commercial cultivars (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…napus pathosystem provide experimental evidence for a fungal pathogen that it may be possible to predict durability of R genes introduced into new cultivars by assessing the fitness cost of virulence. This supports theoretical evidence and experimental evidence with bacterial pathogens (Leach et al 2001;Pringle and Taylor 2002;Pietravalle et al 2006;Bent and Mackey 2007). The evidence that fitness cost of virulence at the AvrLm4 locus is generally greater than that at the AvrLm1 locus suggests that the corresponding resistance gene Rlm4 may be more durable than Rlm1 when it is deployed in commercial cultivars (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…have a fitness cost). Evidence in support of this hypothesis comes from theoretical modelling (Pietravalle et al 2006) and from experimental work with bacterial pathogens (Leach et al 2001) but there has been little experimental work done with fungal pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The durability of major gene resistance may be increased by diversification schemes, which classify the current commercial cultivars by the resistance genes they carry, to guide strategies for deployment of these genes (Gladders et al, 2006). Modelling the effects of different deployment strategies in both space (pattern of areas sown to cultivars with different genes) and time (seasonal pattern of deployment), in relation to different measures of durability of resistance (van den Bosch and Gilligan, 2003), can be used to guide advice on effectiveness of different proposed deployment strategies (Pietravalle et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that loss or mutation of avirulence alleles by pathogens to render resistance ineffective usually carries a fitness cost, and although it has been demonstrated less frequently for fungal pathogens than for bacteria (White et al 2000), this phenomenon has been demonstrated in the L. maculans--B. napus pathosystem (Huang et al 2006). It is useful to know whether this is the case for a particular resistance gene when deciding on the best resistance management strategies by which to deploy it (Pietravalle et al 2006) with the aim of improving resistance to P. brassicae in commercial oilseed rape cultivars and decreasing fungicide use.…”
Section: Measurement Of B Napus Resistance To P Brassicaementioning
confidence: 99%